Features of Unilateral Hearing Loss Detected by Newborn Hearing Screening Programme in Different Regions of Turkey - Genc, Gulsum Aydan; Konukseven, Ozlem; Muluk, Nuray Bayar; Kirkim, Gunay; Basar, Figen Suren; Tuncer, Ulku; Belgin, Erol (Elsevier Sci Ltd, 2013)
Objective: Newborn hearing screening (NHS) works well for babies with bilateral hearing loss. However, for those with unilateral loss, it has yet to be established some standard rules like age of diagnose, risk factors, hearing loss degree. The aim of this study is to identify the demographic characteristics of newborns with unilateral hearing loss to obtain evidence based data in order to see what to be done for children with unilateral hearing loss (UHL). Method: Newborn hearing screening data of 123 babies with unilateral hearing loss, 71 (57.7%) male and 52 (42.3%) female, were investigated retrospectively. Data provided from the archives of six referral tertiary audiology centers from four regions in Turkey. Data, including type of hearing loss; age of diagnosis; prenatal, natal and postnatal risk factors; familial HL and parental consanguinity was analyzed in all regions and each of the Regions 1-4 separately. Result: The difference between data obtained in terms of gender and type of hearing loss was detected as statistically significant (p < 0.05). While UHL was significantly higher in females at Region I, and in males at other Regions of 2-4; SNHL was the most detected type of UHL in all regions with the rate of 82.9-100.0%. There were not significant differences between regions in terms of the degree of hearing loss, presence of risk factors, family history of hearing loss, age at diagnosis and parental consanguinity (p > 0.05). Diagnosis procedure was completed mostly at 3-6 months in Region 4; whereas, in other regions (Regions 1-3), completion of procedure was delayed until 6 months-1 year. Conclusion: This study indicates that the effect of postnatal risk factors, i.e. curable hyperbilirubinemia, congenital infection and intensive care is relatively high on unilateral hearing loss, precautions should be taken regarding their prevention, as well as physicians and other health personnel should be trained in terms of these risks. For early and timely diagnosis, families will be informed about hearing loss and NHS programme; will be supported, including financial support of diagnosis process. By dissemination of the NHS programme to the total of country by high participation rate, risk factors can be determined better and measures can be increased. Additionally, further studies are needed with more comprehensive standard broad data for more evidence based consensus. (c) 2012 Elsevier Ireland Ltd. All rights reserved.
Keywords: Newborn Hearing Screening (NHS) Programme; Unilateral Hearing Loss (UHL); Risk Factors; Consanguinity; Familial Hearing Loss